Best Answer

Due to limitations with browsers mathematical operators (especially + =) get stripped from questions (leaving questions with not enough information to answer them) and it is not entirely clear what the log4 bit means.

I guess that the log4 bit is logarithms to base 4 of 2x^16 (which I'll write as log_4(2x^16) for brevity). If this is so, use normal algebraic operations to make log_4(2x^16) the subject of the equation.

With logs there are useful rules; given 2 numbers 'a' and 'b':

log(ab) = log(a) + log(b)

log(a^b) = b × log(a)

Which means:

log_4(2x^16) = log_4(2) + log_4(x^16) = log_4(2) + 16 × log(x)

and the equation can be further rearranged:

log_4(2x^16) = <whatever>

→ log_4(2) + 16 × log(x) = <whatever>

→ log(x) = (<whatever> - log_4(2)) / 16

Logarithms tell you the power to which the base of the logarithm must be raised to get its argument, for example when using common logs: lg 100 = 2 since 10 must be raised to the power 2 to get 100, ie 10² = 100. (lg is the abbreviation for logs to base 10; ln, or natural logs, is the abbreviation for logs to the base e.) With logs to base 4, it is 4 that is raised to the power of the log to get the original value. eg log_4(16) = 2 since 4^2 = 16.

log_4(2) can be worked out:

The log to any base of the base is 1 (since any number to the power 1 is itself).

Now 2 × 2 = 2² = 4.

→ log_4(4) = 1

→ log_4(2²) = 1

→ 2 × log_4(2) = 1

→ log_4(2) = ½

→ log(x) = (<whatever> - ½) / 16

Back to the rearranged equation; with logs to base 4, if you make both sides the power of 4 you'll get:

4^(log_4(x)) = 4^(<whatever>)

→ x = 4^(<whatever>)

which now solves for x.

Study guides

☆☆

Q: How do you solve the equation 5.2 log4 2x16?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

33

x + 52 + 2y + 35 = 3 x + 2y = 3 - 52 -35 x + 2y = -84 Infinite number of solutions, are you sure you posted the correct equation?

Solve algebraically. 52X = 100 X = 100/52 X = 25/13 ---------------- or 1.923076923

Rounding is when you make the number go up by 1 when it is 5 or more in a one digit number. When it is a two digit number, the number in the ones place has to be 5 or more to round up which means to make the number go up. When a number in the ones place is less than 5, you have to make the number goes down. For example, if you have the number 59, you would round up and it would be 60 or if you had the number 52, you would go down and the number would be 50. Rounding is also done after you solve an equation. For example, when you have an equation like 25+61, you would first have to solve the equation normally and then you round the answer. 25+61=86. 86 is rounded to 90 and that is your answer for an equation that is needed to be rounded. Estimating is when you have an equation and you round up or down before you solve the equation.

x + 3x = 52 4x = 52 x = 13 Mrs. Computer is 39 and Mousy is 13. To solve this problem I gave each of the people a representative letter. Mrs Computer = C and Mousy = M The first statment "Mrs Computer is 3 times older that her daughter Mousy" translates to this C=M*3 The second statement "the sum of their ages is 52" translates to this M+C=52 Because we know that C=M*3 I can translate "How old is Mousy" to this equation M+3*M=52 which simplifies to this 4*M=52 then further to this M=52/4

Related questions

The function or equation is required to solve this.

To turn the fraction into a decimal, simply solve the equation. 52/8 means 52 divided by 8. The answer is 6.5.

subtraction; 80-y= 52. 28+52 =80

33

if you want to "solve" this equation, you need an equals sign somehwere! For example, if the problem was 2x - 52=5 then you could solve. You add 52 (or 25) to both sides so the equation becomes 2x = 30. Then you divide both sides by 2 to get x=15

to solve 18-70 you would subtract just like any other equation. 18-70 is equal to a negative number, -52.

-6z + 16 = 52 subtract 16 from each side -6z = 36 divide by -6 z = -6

To solve an equation, use the order of operations in reverse:7k-52 = 9(addition)7k = 61(division)k = (61/7) or ~8.71

13 + 52 = 65

-52. You can solve it using the equation 5 - x = 57 where x is the number that must be deducted from 5 to get 57. 5 = 57 + x x = -52.

With great difficulty because it is not a quadratic equation or even a quadratic expression.

x + 52 + 2y + 35 = 3 x + 2y = 3 - 52 -35 x + 2y = -84 Infinite number of solutions, are you sure you posted the correct equation?

People also asked